2014
DOI: 10.1111/fcsr.12096
|View full text |Cite
|
Sign up to set email alerts
|

Theses and Dissertations Completed in Family and Consumer Sciences: 2013

Abstract: The annual survey of graduate programs at US universities and colleges was conducted in the spring of 2014 to compile a list of theses and dissertations completed in 2013 in family and consumer sciences areas of interest. For the survey, requests for the titles and authors were sent via e-mail to institutions three times within a 6-week period. Thirty-nine colleges and universities responded to the survey. A total of 307 theses and 173 dissertations were reported. A report of those submissions, by subject cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Therefore, Mastrangelo et al (2014) noted that the element of attitude present in the extended TPB directs the complete evaluation of the specific behaviour in the perspective of the farmer's intention towards the adoption of GFT, and attitude is the term that is defined as a positive or negative assessment of the adoption behaviour. As Kabaci (2014) observed, in many studies, attitude is an important variable (anterior) of behavioural intention. For example, Martey et al (2014) surveyed a national base to find out the farmers' intention towards the adoption of GFT, and they found that farmers having positive attitudes towards environmental concerns are more willing to adopt GFT.…”
Section: Conceptual Framework and Hypothetical Relationshipmentioning
confidence: 82%
“…Therefore, Mastrangelo et al (2014) noted that the element of attitude present in the extended TPB directs the complete evaluation of the specific behaviour in the perspective of the farmer's intention towards the adoption of GFT, and attitude is the term that is defined as a positive or negative assessment of the adoption behaviour. As Kabaci (2014) observed, in many studies, attitude is an important variable (anterior) of behavioural intention. For example, Martey et al (2014) surveyed a national base to find out the farmers' intention towards the adoption of GFT, and they found that farmers having positive attitudes towards environmental concerns are more willing to adopt GFT.…”
Section: Conceptual Framework and Hypothetical Relationshipmentioning
confidence: 82%